A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil - Nascimento, Elielton; Cavalcanti, Thaynã; Pinheiro, Ulisses (Zootaxa, 2019)
Acanthella Schmidt, 1862 species are characterized by choanosomal skeleton of dendritic tracts cored by interwoven sinuously bent strongyles or strongyloxeas and echinated by straight styles, oxeas or anisoxeas (Van Soest et al. 2002). The genus Acanthella comprises 33 valid species, with six known from the Atlantic Ocean (Van Soest et al. 2018). Previously, the only record for Brazil was A. flagelliformis (Van Soest & Stentoft, 1988) (Muricy 2018). Species of the genus include a transition from shrub like ‘Axinellas’ and herbaceous species similar to the genus Suberites Nardo, 1833 (Schmidt 1862; Vosmaer 1912). Due to its heterogeneous complex of species, Acanthella has been confused with other axinellids. Similarities were seen in genera such as Phakellia (Van Soest et al. 2002), which shares spicule complement and comparable choanosomal skeletons. In the present study, we describe a new species of Acanthella from oceanographic expeditions of the northeast region of Brazil. Two specimens of Acanthella sp. nov. were collected by dredging at Ceará and Pernambuco State, Brazil. All specimens were preserved in 92% ethanol and deposited in the Porifera Collections at the Universidade Federal de Pernambuco (UFPEPOR). The taxonomic identification was carried out through analysis of spicules morphologies, using Light Microscopy (LM) and Scanning Electron Microscopy (SEM), following methods described by Hajdu et al. (2011).